Does coercive pressure improve construction quality? The mediating role of organizational learning - Song, Zhi-hong; Chen, Yangyuan; Lee, Dong-mei (Advances in Social Sciences Research Journal, 2018)
Combining institutional theory and organizational learning theory, the article develops a conceptual model which describes the relationships among coercive pressure, organizational learning, and construction quality. Data were then collected via 268 valid questionnaires from construction firms located in Taiyuan in central China. Hypotheses in the conceptual model were tested with structural equation modeling. The empirical results reveal that: (1) coercive pressure has a significant positive impact on organizational learning; (2) organizational learning has a significant positive impact on construction quality; (3) organizational learning mediates the relationship between coercive pressure and construction quality. The empirical results may provide implications for Chinese construction firms aiming at improve construction quality.